Large mammal diversity matters for wildlife tourism in Southern African Protected Areas: Insights for management - (:unkn) unknown (My University, 2018)
Relationships between biodiversity and cultural ecosystem services have been little studied compared to other ecosystem services, although fundamental for environmental management. Recreational ecosystem services like wildlife tourism are specific cultural ecosystem services that often involve relationships between the supply of opportunities to interact with biodiversity and the demand of wildlife tourists. Here, we first investigated whether different biodiversity measures based on three metrics applied to four components of large mammal diversity influenced the distribution of visitors within four Protected Areas (PAs) in Southern Africa. Second, we explored whether these effects were context-specific across the four PAs. We counted large mammals and visitor numbers along 196 road transects to test these relationships. All species-mammal diversity metrics related positively to visitor numbers. Subsets of mammal diversity were also positively associated with the distribution of visitors in all PAs. Relationships between supply and demand for the recreational service of wildlife tourism were mainly context-specific: the relationships between biodiversity measures and visitor numbers differed among PAs. Our results could help managers to optimize the use of recreational services within PAs, by diversifying viewing opportunities while reducing disturbance to wildlife. The supply-demand approach presented here offers promising avenues for further assessments of recreational ecosystem services.
Keywords: African Research